Pelatihan Media Cmaptool dalam Pembelajaran Menghadapi Tantangan Era Revolusi 4.0 - Desy Eka Muliani; Widya Widya; Zaturrahmi Zaturrahmi; Yeni Nurpatri; Yusmanila Yusmanila; Ena Suma Indrawati (Jurnal Pengabdian Masyarakat (abdira), 2021)
The era of the Industrial Revolution 4.0 has had a significant impact in the world of education, educators are required to master technology and use it to support learning towards digitalization. The ability of educators at SMPN 41 Padang in making learning media is still not varied, in general they still use powerpoint. The service was carried out in one day at SMPN 41 Padang, attended by all teachers at SMPN 41 Padang, this service in the form of cmaptools media training went smoothly, starting with the delivery of material by the resource person then the next session was the practice of making cmaptools media. With this cmaptools media training, it is hoped that teachers will be skilled in making more innovative, varied and interactive learning media. IT-based learning media is needed in the industrial revolution era 4.0.